KYAI, POLITICS AND DAKWAH PATTERNS: READING POLITICAL NARRATIVES IN RELIGIOUS SPACES (STUDY IN BANTEN) - Hasanah, Umdatul; Purwanti, Eneng (Al Qalam, 2020)
The involvement of kiyai in political life can be seen from various sides, both in religion and politics itself. From the religious side, the involvement of religion leaders in political dynamics could be seen to strengthen religious life because of political support. Meanwhile, from the political side it could also be seen to provide a positive point for political life because of the content of religiosity and morality. However, the involvement of the kyai in political dynamics is seen to have reduced his central position as a reference for religious behavior and sources of knowledge for all groups without barriers, while political traditions often divide. The relationship between politics and religion often makes religious instruments become a part that frames or become a political packaging, both the person, the institution and the activities including the activities of dakwah. Through observation and in-depth interviews, it was found that the use of religious spaces and dakwah patterns were still regarded significant in socializing and building awareness including political choices. Even though there is political narratives in the activities of dakwah, it does not undermine the marwah and glory of the dakwah itself. Political content and narratives in the religious space is only as distractions in affirming their choices, it is not found any elements of manipulation or politicization which distort the religious itself. This happened along with social control through communication technology. In addition, people are more intelligent and critical, as well as there are variety of references that made people have many choices in determining their attitudes including political choices.